Modern Japan : - Cortazzi, Hugh (Bodley Head, 1993)
After a brief description of Japan's geography, people and language, and a summary of Japanese history and culture, this book gives an account of the Japanese constitution, the Diet and the organization of government (central and local). Separate chapters follow on law and order, foreign affairs and defence, industry and commerce, agriculture and infrastructure, employment, health and welfare, and finally, education and culture. Seven appendices provide additional facts and figures. Sir Hugh Cortazzi is the author of "The Japanese Achievement".